2013
DOI: 10.1109/tgrs.2012.2211606
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Estimation of Rain Microphysical Parameters From X-Band Dual-Polarization Radar Observables

Abstract: Modern polarimetric weather radars typically provide reflectivity, differential reflectivity, and specific differential phase shift, which are used in algorithms to estimate the parameters of the rain drop size distribution (DSD), the mean drop shape, and rainfall rate. A new method is presented to minimize the parameterization error using the Rayleigh scattering limit relations multiplied with a rational polynomial function of reflectivity-weighted raindrop diameter to approximate the Mie character of scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…Z H , K dp , and Z DR were calculated for these DSDs for the MXPol stacked PPI incidence angles; temperatures of five, 10, and 15 • C; and each of four drop axis ratio functions: those of Andsager et al (1999); Brandes et al (2002); Thurai et al (2007), and that of Beard and Chuang (1987) in the form shown in Kalogiros et al (2013). Unusual records with Z DR or K dp less than or equal to zero (0.16 % of all simulated radar records) were excluded.…”
Section: Double-moment Dsd Normalisationmentioning
confidence: 99%
See 4 more Smart Citations
“…Z H , K dp , and Z DR were calculated for these DSDs for the MXPol stacked PPI incidence angles; temperatures of five, 10, and 15 • C; and each of four drop axis ratio functions: those of Andsager et al (1999); Brandes et al (2002); Thurai et al (2007), and that of Beard and Chuang (1987) in the form shown in Kalogiros et al (2013). Unusual records with Z DR or K dp less than or equal to zero (0.16 % of all simulated radar records) were excluded.…”
Section: Double-moment Dsd Normalisationmentioning
confidence: 99%
“…(9), the reflectivity-weighted mean drop axis ratio, r z , is related to a negative power of the differential reflectivity in linear units. In Kalogiros et al (2013), the reflectivity-weighted and mass-weighted drop axis ratios were assumed to be the same and differences were dealt with through fitting of qualitative relationships between radar variables. A similar approach is taken here.…”
Section: Retrieval Of Dsd Moment Threementioning
confidence: 99%
See 3 more Smart Citations